Coprophagy Prevention Decreases the Reproductive Performance and Granulosa Cell Apoptosis via Regulation of CTSB Gene in Rabbits - Song, Guohua; Wang, Yadong; Wang, Yaling; Jiang, Yixuan; Sun, Shuaijie; Cai, Hanfang; Sun, Guirong; Li, Ming; Bionaz, Massimo; Xu, Huifen (Frontiers in Physiology, 2022)
Coprophagy is an instinctive behavior in rabbit with important effects on growth and reproductive performance. The underlying mechanism of this effect in rabbit is unknown. Here, we used Elizabeth circle as a coprophagy preventing model in female rabbits and assess feed intake, growth, and reproductive performance. We found that preventing coprophagy did not affect feed intake but decreased body weight and weight of several organs and tissues and resulted in complete reproductive failure during the late pregnancy period, accompanied by reduced levels of plasma progesterone. RNA-seq analysis of rabbit ovarian tissues revealed that preventing coprophagy affected significantly 241 genes (DEGs), with the large majority being downregulated. Bioinformatic analyses revealed that those DEGs are mostly involved in apoptosis, immune response, and metabolic pathways. Among DEGs, the lysosomal cysteine protease cathepsin B (CTSB) was significantly downregulated in the coprophagy prevention group. Further studies using siRNA and adenovirus overexpression systems revealed that CTSB promotes the proliferation of rabbit granulosa cells (GCS) and prevents apoptosis. Measurement of transcripts coding for proteins related to apoptosis revealed a minor transcriptomic effect of CTSB, indicating that its effect is likely post-transcriptional. Overexpression of CTSB increased secretion of progesterone and estradiol, partly via upregulation of CYP19A1 while inhibition of CTSB decreased progesterone secretion partly via downregulation of the StAR gene. In conclusion, our study demonstrated the detrimental effect on reproduction by preventing coprophagy with a main role for this response played by CTSB on the granulosa cells of the ovary.